Gathered around the campfire eaudiobook S'mores and stories under the stars. - Carlson, Melody A. (christianaudio, 2020)
Whether your idea of camping is in a tiny tent, a luxury RV, or somewhere in between, nothing beats having fun with family and friends in the fresh air. Relive favorite memories of childhood vacations and get excited for future outdoor adventures with these humorous and heartwarming recollections from bestselling author and camping enthusiast Melody Carlson. Pack your gear and hit the road with Melody as you encounter: Campfire Connections-how a simple offer of firewood sparks a friendship. Lolly the Bear-an unexpected guest with a sweet tooth pays a morning visit. The Worst Camping Trip Ever-a pregnant woman and a torrential downpour make for a hasty midnight departure. Best-Laid Plans-all it takes is one unhappy camper to spoil an outing. Fireworks on the Fourth-an explosive clash between generations ends with a promise of unconditional love. Along the way, you'll enjoy inspirational quotes and practical tips to make your next camping experience even "s'more" of a success. So gather 'round and get ready for some unforgettable stories.